Analysis of 100 most cited articles on forensic odontology - Namrata Sengupta; Sachin C. Sarode; Gargi S. Sarode; Amol R. Gadbail; Shailesh Gondivkar; Sneha Patil; Shankargouda Patil (Saudi Dental Journal)
Objectives: Bibliometric analysis of best-cited papers brings awareness about the influential publications and trends in the literature on a particular topic. This will help not only the researchers and academicians but also the students for selecting quality landmark articles. With this view in mind a bibliometric analysis was performed to identify the 100 top-cited papers on Forensic Odontology (FO) in the literature. Materials and methods: A search was performed using Scopus database in August 2019. The articles were further reviewed and basic standard information related to bibliometric analysis was recorded. Results: The 100 most cited articles were published from 1985 to 2014 (77% published after 2001). The most frequently cited article received 259 citations, whereas the least received 31 (mean citations 58.78 ± 33.14). There were 16 different journals with Forensic Science International having the most number of articles (n = 36). One author had 16 articles while 8 authors had 4 or more articles published in the top 100 list. Belgium was the country with most number of articles (n = 17) followed by United States (n = 16). In terms of document type, 87 were original research, 7 conference papers and 6 reviews. Five organizations funded 5 of the top 100 articles. Katholieke Universiteit Leuven, Belgium affiliated the most documents (n = 16). Majority of the papers were related to age estimation (46) followed by victim identification (30), mass disaster (9), bite mark analysis (8), sex determination (5), race determination (4), dental DNA analysis (3), palatal rugae pattern (2) and lip prints (1). Conclusion: This is first of its kind citation analysis of the 100 most cited articles in the field of FO. The results of this paper will help the researchers, academicians and students for appropriate article referrals.